Financial Crisis and Credit Crunch as a Result of Inefficient Financial Intermediation-with Reference to the Asian Financial Crisis - Chen, Zhaohui (IMF Working Papers; Working Paper, 1998)
This paper develops a model of private debt financing under inefficient financial intermediation. It suggests a mechanism that can generate the following sequence of events observed in the recent Asian crisis: A period of relatively low capital flow despite a steady improvement in economic fundamentals (capital inflow inertia), followed by a fast buildup of capital inflow, and ended with a large capital outflow and domestic credit crunch. Unlike other models requiring large movements in fundamentals or asset prices to explain a financial crisis, this model can exhibit large credit/capital flow swings with moderate changes in the economic and market environment.